Competence Improvement Training for Physical Education Teacher at Darussalam Pasuruan Islamic Boarding School - Irma Febriyanti; Mochamad Ridwan; Sapto Wibowo; Rahmawati Al Adha Nikmah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
Physical Education, Sports, and Health plays a crucial role in supporting physical development, character building, and a healthy lifestyle. However, Islamic boarding school-based educational institutions still face challenges related to limited teaching competencies among physical education teachers, particularly those without formal physical education backgrounds. This condition impacts the quality of learning, resulting in unstructured and monotonous teaching that hinders the achievement of learning objectives. This community service program aims to improve the pedagogical and professional competencies of physical education teachers in Islamic boarding schools through module-based training and mentoring. The program was implemented through needs analysis, module development, workshops, teaching practice assistance, and evaluation. Participants included four physical education teachers and fifteen community service teachers from Islamic boarding school backgrounds. Results showed that the module-based training improved teachers' understanding of basic Physical Education, Sports, and Health concepts, as well as lesson planning skills and structured teaching practices. Participants responded positively, with a 100% satisfaction rate, and considered the module a practical teaching guide. These findings confirm that module-based training is effective and essential for improving the competency of physical education teachers in Islamic boarding schools.